(3LfI GdQVG aj GdJSdje deG bOQg Gddg hbVis - (3eMeO Hf eMeO Hf eMeO GHf YGUe GdbjSj GdCfOdSj GdZQfGWj, CHhjMji,J (B857 (3g` s ((3eMeO Hf MSf s)
(3ChdgG (B:s
(3abGd dg GdhGKb QMeg Gddg aJbHd efG UdI JSJYjf HgG Ydi OgQc s
(3BNQgG (B:s
(3hGdMeO ddg HGdeMGeO GdJi jKfi HgG Ydi faSg ced s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3fSNI eUMMIs
(3HBNQgG MQR GdCbSGe dSjOi eMeO fXe ai (B4 (3hQbGJ s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
Keywords: (3GdJUha hGdBOGH GdTQYjIs